(untitled) (Indonesian Theological Justice Review, 2024)
Islamic theology has a profound impact on how justice is perceived and practiced in Indonesia, especially in addressing issues of poverty and inequality. This paper explores key Islamic theological concepts, such as zakat (charity), sadaqah (voluntary charity), and tithing, and their role in promoting social justice and alleviating poverty in Indonesia. The study examines how religious leaders and scholars interpret these concepts in relation to contemporary social issues such as economic inequality, access to healthcare, education, and basic needs. By analyzing religious texts and contemporary Islamic teachings, the paper demonstrates that Islam’s emphasis on social justice can be a powerful tool for addressing economic disparities and improving the welfare of marginalized communities. However, it also acknowledges the complexities of implementing these teachings in a pluralistic society, where political, cultural, and economic factors complicate the pursuit of justice. The paper argues that Islamic theology, when understood and applied effectively, can play a pivotal role in creating a more equitable society in Indonesia. Recommendations include enhancing Islamic education on social justice, strengthening institutional mechanisms for distributing zakat, and promoting the active role of religious communities in addressing systemic inequality.